THE EFFECT OF QUEEN AGE AND QUEEN EXCLUDER ON SOME BIOLOGICAL ACTIVITY OF HONEYBE (Apis mellifera) COLONIES - Mustefa, Abdurahim O.; Abdulla, Yasseen M.; Sallow, Mohammed H. (Diyala Agricultural Sciences Journal, 2018)
This study had been conducted in one apiary in Erbil Governorate from 15-32013 to 27-6-2013. The results showed that the Queen excluder (which used between brood and honey chamber) and Queen age has had a significant effect in above activity which showed the superiority of A2 treatment leaded by young queen age one year without using Queen excluder which recorded the highest means of bee population, worker brood area, pollen area and sealed honey area were 12.9 frames bee, 679.5 sq. inch, 210 sq. inch and 791.1 sq. inch respectively compared with A3 treatment leaded by old queen 2 years age with using Queen excluder were recorded lowest mean 9.6 frame bee, 459.2 sq. inch, 97.8 sq. inch and 351.1 sq. inch respectively, but the A2 treatment recorded the lowest mean of Drone brood area was 21. sq. inch compared with the highest mean in A4 treatment was 51.8 sq. inch.